2004
DOI: 10.1002/ajim.20116
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among Ontario members of the International Union of Bricklayers and Allied Craftworkers

Abstract: Bricklayers and Allied Craftworkers are at risk from diseases associated with heavy exposure to inorganic dust: lung cancer, stomach cancer, and pneumoconiosis. Dust control as well as education and training of these workers to protect themselves against inhalation hazards is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Our results are supported by a study of Lithuanian cement masons, 45 and a study of US cement-producing workers, 46 while no clear associations were found in other studies of cement workers in Sweden or the US. 47, 48 The positive association between quartz dust and risk of gastric cancer found in our study is in line with reports on workers exposed to silica dust in Canada, [49][50][51] Spain 28 and Japan. 52 The current large and prospective cohort study design that revealed positive, dose-response associations regarding both cement dust and quartz dust provides valid support in favor of true relations between these exposures and gastric cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are supported by a study of Lithuanian cement masons, 45 and a study of US cement-producing workers, 46 while no clear associations were found in other studies of cement workers in Sweden or the US. 47, 48 The positive association between quartz dust and risk of gastric cancer found in our study is in line with reports on workers exposed to silica dust in Canada, [49][50][51] Spain 28 and Japan. 52 The current large and prospective cohort study design that revealed positive, dose-response associations regarding both cement dust and quartz dust provides valid support in favor of true relations between these exposures and gastric cancer.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, they found an elevated SIR for cancer of the cardia of the stomach for individuals employed as bricklayers during the 1960-1970 (1.8 (95% CI: 1.2-2.5)) or 1970-1980 (1.9 (95% CI: 1.2-2.7)). Dong et al [1995] and Finkelstein and Verma [2005] did not find an increased risk for stomach cancer for bricklayers compared to other construction workers.…”
Section: Neoplasmsmentioning
confidence: 63%
“…Three articles gave information regarding lung cancer [Dong et al, 1995;Robinson et al, 1995;Finkelstein and Verma, 2005]: a statistically significant elevated prevalence (PMR: 120 (95% CI: 106-137); 134 (95% CI: 112-151)) was found in two studies comparing bricklayers to the general population [Dong et al, 1995] or other construction workers [Robinson et al, 1995]. Finkelstein and Verma [2005] did not find an increased risk for bricklayers compared to plumbers.…”
Section: Neoplasmsmentioning
confidence: 95%
See 1 more Smart Citation
“…52 Dust-exposed workers such as bricklayers have shown increased risks, not only for pneumoconiosis and lung cancer from silica, but also for stomach cancer. 53 The potential problems of construction workers' exposures to diesel exhaust have also been flagged. 54 Other cancers may be associated with construction work; a recent Canadian study of occupational risk factors for brain cancer, for example, found an increased risk among construction workers.…”
mentioning
confidence: 99%